NEW TRENDS IN THE DEVELOPMENT OF FOREIGN DIRECT INVESTMENT AND THEIR IMPACT ON THE ECONOMIC SECURITY OF THE HOST COUNTRY - Madumarov Khusniddin Komilovich (Modern American Journals, 2025)
This thesis analyzes the emerging trends in foreign direct investment (FDI), including digitalization, sustainability, geopolitical fragmentation, and regulatory tightening, and their multifaceted impact on the economic security of host countries. Drawing on widely cited empirical studies, it highlights both the positive effects—such as technology transfer, job creation, and infrastructure development—and the associated risks, including overdependence, national security threats, and environmental degradation. The paper recommends balanced FDI governance, institutional strengthening, and sustainable investment promotion as key policy priorities.
Keywords: Foreign direct investment (FDI), economic security, digitalization, green economy, national sovereignty, infrastructure, regulatory policy, emerging markets, risk mitigation.